Design of Heat Exchanger for The Production of SnO2 Nanoparticle - Yohanes Ivan Benaya Parlindungan Nainggolan; Asep Bayu Dani Nandiyanto (Konsorsium LPPM Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2022)
This study's objective is to examine the design of a heat exchanger for the production of SnO2 nanoparticles by calculating the shell and tube heat exchanger's dimensions. In order for the design to be well-directed, several steps must be taken, including determining the heat exchanger's dimensions and material requirements using standards, computing the main shell and tube components, and computing the heat exchanger's performance. Microsoft Excel is used for heat exchanger data processing. One shell and two tubes were used in the design of the heat exchanger. The results of the designed HE have a shell diameter of 0.84 m, a tube length of 7.315 m, and an inside diameter of 0.021 m. The flow type of HE is turbulent, with a heat transfer efficiency of 48.05 percent and a fouling factor of 0.0015195 m2Â·K/W, the device generates a heat transfer rate of 958198.91 W. This study demonstrates that the heat exchanger has a successful, high-performing design. This design can be used as a model for creating a heat exchanger that is more cost-efficient, efficient, and reliable.